The in-vitro Antioxidant Properties of Crude Drugs Traditionally Used for Diabetes Management in Northern Banyumas - Dwi Hartanti; Shintia Lintang Charisma; Widya Agustina; Rizky Destya Sary; Denia Awanda Putri; Alwani Hamad (Faculty of Pharmacy, Universitas Gadjah Mada, 2022)
Chinaberry (Melia azedarach L.) leaves, Malayan cherry (Muntingia calabura L.) fruits, and Yacon (Smallanthus sonchifolius (Poepp.) H.Rob.) leaves are used for traditional diabetes treatment by Banyumas (Central Java, Indonesia) people. This study characterized selected quality parameters, evaluated the in-vitro antioxidant activity as the preliminary assay for its antidiabetic activity, and calculated the total flavonoid content (TFC) and total phenolic content (TPC) of those crude drugs. The plant materials of each species were collected from three different areas in Banyumas and dried into crude drugs. The quality parameters were determined according to the standard method in the Indonesian Herbal Pharmacopeia (IHP) 2017. The antioxidant activity was evaluated by the standard 2,2-diphenyl-1-picrylhydrazyl (DPPH) scavenging and ferric reducing antioxidant power (FRAP) assays, while TFC and TPC were analyzed following standard methods in IHP 2017. The correlations between antioxidant activities and the TFC-TPC were analyzed by Pearson's correlation test. The values for acid-insoluble ash, loss on drying, total ash, ethanol extractable, and water-extractable of all crude drugs were quantified, with TPC and TFC proposed as the chemical content parameter for Malayan cherry fruits and Yacon leaves. Yacon leaves and Malayan cherry fruits contained the highest TFC and TPC at 8.01±0.72 mg Quercetin equivalent (QE)/g dry weight (DW) and 11.54±1.44 mg Gallic acid equivalent (GAE)/g DW, respectively. Malayan cherry fruits exerted the strongest DPPH scavenging activity (366.13±17.65 mM Trolox equivalent (TE)/g DW) and FRAP (1025.33±50.47 mM TE/g DW). Moderate to strong correlations were observed between DPPH radical scavenging activity – FRAP and TFC-TPC of Malayan cherry fruits and Yacon leaves. Hence, flavonoids and phenolic compounds of both crude drugs contributed to their antioxidant activity.